ENGLISH TEACHING METHODS IN WRITING DESCRIPTIVE TEXT OF SMK NEGERI 1 PULAU RAKYAT - Suriya Ningsih; Rahmad Husein; Nora Ronita Dewi (Universitas Negeri Medan, 2018)
This study was aimed to describe the English Teaching Methods in writing descriptive text and the problems faced by the teacher. This study was conducted by using descriptive qualitative research design. The subject of this research was an English teacher of SMK NEGERI 1 Pulau Rakyat. The techniques of collecting data were by observing the process of teaching writing comprehension of descriptive text at X Grade students and interviewing the English teacher. The techniques of collecting data were observation and interview. This study found that the teacher at SMK NEGERI 1 Pulau Rakyat used the method in teaching writing descriptive text. The English teacher used the lecture method and discussion method to teach in the descriptive text and the students get difficulties in comprehending the material. The application lecture method and discussion method is not appropriate with scientific approach of 2013 Curriculum. The result and response from the students to the teacher’s method are still not effective. The teacher should not apply the methods in written but also in spoken. And the problems faced by the teacher were the first is about the lack of students’ vocabularies, and the second is about the students’ participations when work in group. This study also found that the teacher’s methods not integrated with the scientific approach of 2013 Curriculum. The implementation of methods in teaching writing should can make teaching learning process more interesting and help the students’ understanding and skill of writing comprehension better.Key words: Teaching Method, Writing, Descriptive Text.